Analisis Hubungan Polifarmasi Dengan Potensi Interaksi Obat Pada Peresepan Pasien Diabetes Melitus Tipe 2 - Mulyani, Yani; Siti Balqis, Salwa; Sutrisno, Entris; Anggriani, Ani (JURNAL FARMASI GALENIKA, 2024)
The IDF estimates that the prevalence of diabetes mellitus based on age will continue to increase from 2021 to 2045 (24.0% vs 24.7%). Patients with diabetes mellitus have comorbidities that result from elevated blood glucose levels, leading to polypharmacy and potential drug interactions. This study aims to determine the percentage of drug interactions and the relationship between polypharmacy and the potential for drug interactions in patients with type 2 diabetes mellitus at RSU Rama Hadi Purwakarta. The study was conducted using a cross-sectional, retrospective method, analyzing prescriptions of patients with type 2 diabetes mellitus at RSU Rama Hadi from September 1 to 30, 2022. Prescriptions were identified for interaction types and severity using drugs.com, Medscape, and Stockley's Drug Interaction Handbook, 9th edition, with results analyzed using Fisher's exact test. The study found that patients aged 56-65 years (40.1%) were more likely to suffer from type 2 diabetes mellitus, with females having a higher incidence compared to males (70.7% vs 29.3%). Among 147 prescriptions, 97% had drug interactions, with moderate severity predominating (97.8%), and pharmacodynamic interactions being the most common (76%). Fisher's exact test revealed a p-value of 0.001 (p < 0.005). Thus, it can be concluded that there is a significant relationship between polypharmacy and the potential for drug interactions in the prescriptions of type 2 diabetes mellitus patients at the pharmacy department of RSU Rama Hadi Purwakarta.